PENDAMPINGAN SISTEM PEMBUKUAN AKUNTANSI SEDERHANA PADA PETANI UBI DI KECAMATAN DUMAI BARAT KOTA DUMAI - Fazli, Muhammad; Fernando; Mihairy, Vallerina (Komunitas Manajemen Kompetitif, 2025)
This community service program was implemented to enhance the ability of cassava farmers in Dumai Barat District to perform financial record-keeping through the application of simple accounting bookkeeping. The main issue identified is the farmers’ low financial literacy, which leads to irregular transaction records, difficulties in calculating production costs, and the inability to prepare basic financial statements. The activities were carried out through several stages, including field observation, introduction to basic accounting concepts, hands-on training in simple bookkeeping, and continuous mentoring using daily cash books. The results indicate a significant improvement in farmers’ understanding and skills in recording income, expenses, and calculating the cost of goods manufactured (COGM). Farmers have become more capable of managing and evaluating their agricultural activities systematically. This mentoring program is proven effective in improving financial management quality and encouraging farmers to develop their agricultural businesses in a more modern, independent, and sustainable manner. Keywords: simple bookkeeping, cassava farmers, accounting, mentoring, production cost